KAJIAN GENDER TERHADAP PELUANG USAHA DI WEB: PERILAKU INFORMASI PADA MASYARAKAT DESA GIRIMULYA KECAMATAN CIBUNGBULANG KABUPATEN BOGOR - Ade Abdul Hak (Pusat Studi Gender dan Anak (PSGA), Universitas Islam Negeri Syarif Hidayatullah, 2015)
This research investigated the differences of information behavior between men and women in Girimulya, Cibungbulang, Bogor. It is important to know the effectiveness of the “WEB desa” as one of information resources of business opportunities. It has been developed by UIN students as one of KKN programs.The approach used in this research was TAM model that was based on the constructs of perceived ease of use (PEOU), perceived usefulness (PU), and behavioral intention (BI). Questionnaires of 100 samples (50 men and 50 women) collected with the random sampling approach were analysed using SPSS version 22. The result showed that the mean score for all of the constructs was high out of maximum score obtainable of 4 (very high), except to the behavioral intention (BI)which was very high and still different to men’s was higher than women’s. T-Test analysis indicated that there was positive and significant effect for each construct, except the perceived ease of use (PEOU)to the behavioral intention (BI). Meanwhile, the most occurred in the effect value of the women’s were higher than men. The usefulness becomes more important than easiness in providing “WEB desa”.